THE CHALLENGES OF CITIZEN DIPLOMACY IN NIGERIA PROJECT, 2007-2010 - B. Aleyomi, Michael; B. Abu Bakar, Mohamad (PEOPLE: International Journal of Social Sciences, 2017)
Promoting the general welfare of the people and securing citizens’ liberty is an incontrovertible project of any state’s policymaking. Therefore, Nigeria’s citizen diplomacy is one of the diplomatic drives of achieving this project. However, avid reader and scholar of the Nigerian polity will notice some national and international contradictions that have hampered the promotion of Nigerians’ welfare and security, and thus challenging the positive image perception of the country. Therefore, the task of the paper is tounderscore the challenges clogging the wheel of citizen diplomacy towards achieving Nigeria project, and to enunciate the way forward for Nigeria’s regeneration. Utilizing both primary (direct observations, interviews and focus groups) and secondary (literature and document reviews) methods of data collection, which are qualitatively and systematically analyzed through inductive approach, the study reveals an obvious wide gulf between the Nigerian State and its citizens. The paper posits that this intricately complementary domain aids the country’s image crisis.Among all other things, the paper recommends a comprehensive publicity of the concept of citizen diplomacy and a concerted institutional conspiracy in fighting corruption. Hence, enhancing the welfare of the Nigerian citizens, as well as, improving the rebranding efforts of Nigeria will be a mirage.